Effects of various macroalgae species on methane production, rumen fermentation, and ruminant production: A meta-analysis from in vitro and in vivo experiments - Sofyan, Ahmad; Irawan, Agung; Herdian, Hendra; Jasmadi, Jasmadi; Harahap, Muhammad Ainsyar; Sakti, Awistaros Angger; Suryani, Ade Erma; Novianty, Hilda; Kurniawan, Taufik; Darma, I. Nyoman Guna; Windarsih, Anjar; Jayanegara, Anuraga (Elsevier, 2022)
A meta-analysis was performed to examine the dietary inclusion of marine macroalgae species to target methane (CH4) reduction from ruminant animals and the effects on rumen fermentation and animal performance. A literature search was conducted from global scientific databases, resulting in 25 in vitro and 22 in vivo studies eligible to be integrated in a database. A total of 673 experimental units comprising 537 in vitro and 136 in vivo experimental units were analyzed by using mixed model methodology in SAS and multivariate analysis in R Studio. Principal component analysis (PCA) from in vitro dataset revealed difference effects of brown, green, and red macroalgae on CH4 production without a pronounced pattern on rumen fermentation. Likewise, PCA from in vivo dataset supported the in vitro results whereas Ascophyllum nodosum (brown) and Asparagopsis taxiformis (A. taxiformis; red) species showed noticeably separated clusters on CH4 production. Mixed regression analysis from in vitro and in vivo databases showed interaction effects (P < 0.001) between levels × species on CH4 production and the percentages of acetate (C2), propionate (C3), butyrate (C4) whereas A. taxiformis showed the greatest effects on the decrease of C2 and increase of C3 proportions (P < 0.001), among other species. Additionally, dietary levels of A. taxiformis had strong linear decrease (R2 = 0.946; P < 0.001) on CH4 (g/d) and curvilinear effect on CH4 when expressed as g/kg DMI (R2 = 0.687; P < 0.001). When considering the types of animals, A. taxiformis decreased (P < 0.001) CH4 by 64.76 % in beef cattle but the effect in dairy cows and small ruminant were non-significant (P > 0.05) compared with control diet as a reference. Curvilinear effect on in vitro organic matter digestibility (P = 0.043) and linear degreased on crude protein digestibility (P = 0.029) were found. Feeding macroalgae did not affect dry matter intake (DMI), average daily gain (ADG), milk production and milk composition except for milk lactose which linearly increased (R2 = 0.731; P = 0.002) by increasing Ascophyllum nodosum level. In dairy cows, the inclusion of A. taxiformis increased iodine concentration by more than six-fold increase (P < 0.001) while other species had no substantial effect on iodine concentration. Taken together, macroalgae can be used as feed ingredients for ruminants to decrease CH4 emissions without detrimental effects on metabolism and production performance in ruminant livestock. Notwithstanding, feeding A. taxiformis > 10 g/kg DM of diet may result in an unfavorable effect on the high bromoform and iodine residuals in milk. Future in vivo study using less-explored species that had been tested in vitro need to be conducted.